Asuhan Keperawatan Pada Pasien Diabetes Melitus Dengan Intervensi Terapi Senam Kaki Diabetes Terhadap Penurunan Gejala Neuropati Diabetik - Muhamad Saifudin; Meynur Rohmah; Dwi Wahyuni (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: Diabetes Mellitus is a heterogeneous disorder characterized by increased glucose levels in the blood. Insulin, a hormone produced by the pancreas, controls glucose levels in the blood by regulating its production and storage (Smeltzer and Bare, 2019). Diabetes Mellitus occurs if the pancreas produces little or no insulin so that the sufferer is forever dependent on external insulin, or if the pancreas continues to produce insulin but the body develops immunity to its effects. Diabetic neuropathy is nerve damage caused by increased blood glucose, which results in decreased blood circulation to cells and decreased nerve cell function. Initial symptoms are paresthesia (prickling, tingling or increased sensitivity) and burning (especially at night). As neuropathy increases, the feet feel numb (numb). Decreased sensitivity to pain and temperature puts neuropathy sufferers at risk of experiencing injury and infection in the feet without knowing it (Smeltzer and Bare, 2019). Foot exercises are activities or exercises carried out by Diabetes Mellitus patients which aim to improve blood circulation so that nutrition reaches the tissues more smoothly, strengthen small muscles, calf muscles and thigh muscles, and overcome the limited joint movement often experienced by Diabetes Mellitus sufferers. Method: The method for writing this final scientific paper is a literature review by examining journals that discuss the effect of diabetic foot exercises on reducing neuropathy symptoms in Diabetes Mellitus sufferers. Results: Based on the results of the implementation carried out by the author, namely encouraging patients to carry out routine extremity movements, namely by carrying out diabetes foot exercise therapy for three consecutive days from 09 to 11 January 2024, differences were found between conditions before and after implementation. The patient data before implementation was that the patient said both feet often felt tingling, the patient said both feet sometimes felt like they were numb, the results of scoring symptoms of diabetic neuropathy were 4, while the patient data after implementation was that the patient complained of tingling both times and feeling like numbness. begins to decrease and the results of scoring symptoms of diabetic neuropathy have decreased, namely to a value of 2, so it can be concluded that there is an influence of diabetic foot exercise therapy on reducing symptoms of diabetic neuropathy in diabetes mellitus sufferers. This is in accordance with the journal that the author studied, namely according to Febrina Angraini S, 2020.